Identification of DEAD-Box RNA Helicase DDX41 as a Trafficking Protein That Involves in Multiple Innate Immune Signaling Pathways in a Zebrafish Model - Ma, Jun-xia; Li, Jiang-yuan; Fan, Dong-dong; Feng, Wei; Lin, Ai-fu; Xiang, Li-xin; Shao, Jian-zhong (Frontiers in Immunology, 2018)
DDX41 is an important sensor for host recognition of DNA viruses and initiation of nuclear factor-κB (NF-κB) and IFN signaling pathways in mammals. However, its occurrence and functions in other vertebrates remain poorly defined. Here, a DDX41 ortholog (Danio rerio DDX41, DrDDX41) with various conserved structural features to its mammalian counterparts was identified from a zebrafish model. This DrDDX41 was found to be a trafficking protein distributed in the nucleus of resting cells but transported into the cytoplasm under DNA stimulation. Two nuclear localization signal (NLS) motifs were localized beside the coiled-coil domain, whereas one nuclear export signal (NES) motif existed in the DEADc domain. DrDDX41 acts as an initiator for the activation of NF-κB and IFN signaling pathways in a DrSTING-dependent manner through its DEADc domain, which is a typical performance of mammalian DDX41. These observations suggested the conservation of DDX41 proteins throughout the vertebrate evolution, making zebrafish an alternative model in understanding DDX41-mediated immunology. With this model system, we found that DrDDX41 contributes to DrSTING-DrSTAT6-mediated chemokine (DrCCL20) production through its DEADc domain. To our knowledge, this work is the first report showing that DDX41 is an upstream initiator in this newly identified signaling pathway. The DrDDX41-mediated signaling pathways play important roles in innate antibacterial immunity because knockdown of either DrDDX41 or DrSTING/DrSTAT6 significantly reduced the survival of zebrafish under Aeromonas hydrophilia or Edwardsiella tarda infection. Our findings would enrich the current knowledge of DDX41-mediated immunology and the evolutionary history of the DDX41 family.